Comparison between kinetic and kinetic-kinematic driven knee joint finite element models. Issue 1 (December 2018) - Bolcos, Paul; Mononen, Mika; Mohammadi, Ali; Ebrahimi, Mohammadhossein; Tanaka, Matthew; Samaan, Michael; Souza, Richard; Li, Xiaojuan; Suomalainen, Juha-Sampo; Jurvelin, Jukka; Töyräs, Juha; Korhonen, Rami
Abstract Use of knee joint finite element models for diagnostic purposes is challenging due to their complexity. Therefore, simpler models are needed for studies where a high number of patients need to be analyzed, without compromising the results of the model. In this study, more complex, kinetic (forces and moments) and simpler, kinetic-kinematic (forces and angles) driven finite element models were compared during the stance phase of gait. Patella and tendons were included in the most complex model, while they were absent in the simplest model. The greatest difference between the most complex and simplest models was observed in the internal-external rotation and axial joint reaction force, while all other rotations, translations and joint reaction forces were similar to one another. In terms of cartilage stresses and strains, the simpler models behaved similarly with the more complex models in the lateral joint compartment, while minor differences were observed in the medial compartment at the beginning of the stance phase. We suggest that it is feasible to use kinetic-kinematic driven knee joint models with a simpler geometry in studies with a large cohort size, particularly when analyzing cartilage responses and failures related to potential overloads.